Polymers based on PLA from synthesis using D,L Lactic acid (or racemic lactide) and some biomedical applications : a short review - França, Juliene Oliveira Campos de (2022)
Poly(lactic acid) (PLA) is an important polymer that is based on renewable biomass resources. Because of environmental issues, more renewable sources for polymers synthesis have been sought for industrial purposes. In this sense, cheaper monomers should be used to facilitate better utilization of less valuable chemicals and therefore granting more sustainable processes. Some points are raised about the need to study the total degradability of any PLA, which may require specific composting conditions (e.g., temperature, type of microorganism, adequate humidity and aerobic environment). Polymerization processes to produce PLA are presented with an emphasis on D,L-lactic acid (or rac-lactide) as the reactant monomer. The syntheses involving homogeneous and heterogeneous catalytic processes to produce poly(D,L-Lactic acid) (PDLLA) are also addressed. Additionally, the production of blends, copolymers, and composites with PDLLA are also presented exemplifying different preparation methods. Some general applications of these materials mostly dedicated to the biomedical area over the last 10–15 years will be pointed out.